Problems and prospects of the mechanism of state management of land relations - Vasilieva , Lesya (Pressing Problems of Public Administration, 2024)
The article is devoted to the problems and prospects of the mechanism of state management of land relations. It is emphasized that state management of land relations is necessary in view of the importance of land as a basic resource for ensuring the economic, ecological and social development of the state, the main needs for such management are highlighted: effective use of land resources; guaranteeing property rights and use; ecological sustainability; social balance; economic development; protection of national interests. The article emphasizes that the mechanism of state management of land relations is a key element in ensuring the effective use, protection and distribution of land resources. The main mechanisms of this regulation include legal, economic, administrative and environmental instruments. Problems and issues of a debatable nature regarding the mechanism of state management of land relations are identified, namely: the need to harmonize land legislation, especially in the context of integration into international standards, the choice of the optimal model of land relations management: centralization or decentralization; methods of taxation of land resources; determining the boundaries between economic efficiency and environmental sustainability; centralized control or localized support programs; transparency and prevention of corruption.The tools of an integrated mechanism are proposed to determine the optimal balance between centralized control with uniform standards and flexible localized programs that take into account the specifics of local conditions. We will highlight the areas of improvement of the mechanism of state management of land relations: reforming the regulatory framework; developing institutional infrastructure; optimizing economic instruments; improving the monitoring and control system; developing public-private partnership, integrating the principles of sustainable development.Problems and issues of a debatable nature regarding the mechanism of state management of land relations have been identified, namely: the need to harmonize land legislation, especially in the context of integration with international standards, the choice of the optimal model of land relations management: centralization or decentralization; methods of taxation of land resources; determining the boundaries between economic efficiency and environmental sustainability; centralized control or localized support programs; transparency and prevention of corruption.